Comparative Analysis of Ski Trail Rating in Serra da Estrela (Portugal) and Sierra Nevada (Spain) - Garcia, Raul Ressano (2012)
In Portugal winter tourism is confined to only one mountain called Serra da Estrela. Many Portuguese engage on ski holidays in Spain. The Spanish mountain where more Portuguese skiers go is called Sierra Nevada (Cetursa, 2010). In Europe most of the countries use the same colours to classify the level of the difficulty of the ski slopes. The aim of this paper is to compare the level of the difficulty attributed by the colours of the ski slopes in the Portuguese mountain of Serra da Estrela and the Spanish mountain of Sierra Nevada.